Thermodynamics in Gliomas: Interactions between the Canonical WNT/Beta-Catenin Pathway and PPAR Gamma - Vallée, Alexandre; Lecarpentier, Yves; Guillevin, Rémy; Vallée, Jean-Noël (Frontiers in Physiology, 2017)
Gliomas cells are the site of numerous metabolic and thermodynamics abnormalities with an increasing entropy rate which is characteristic of irreversible processes driven by changes in Gibbs energy, heat production, intracellular acidity, membrane potential gradient and ionic conductance. We focus our review on the opposing interactions observed in glioma between the canonical Wnt/beta-catenin pathway and PPAR gamma and their metabolic and thermodynamic implications. In gliomas, Wnt/beta-catenin pathway is upregulated while PPAR gamma is downregulated. Upregulation of Wnt/beta-catenin signaling induces changes in key metabolic enzyme that modify their thermodynamics behavior. This leads to activation pyruvate dehydrogenase kinase 1(PDK-1) and monocarboxylate lactate transporter 1 (MCT-1). Consequently, phosphorylation of PDK-1 inhibits pyruvate dehydrogenase complex (PDH). Thus, a large part of pyruvate cannot be converted into acetyl-CoA in mitochondria and in TCA (tricarboxylic acid) cycle. This leads to aerobic glycolysis despite the availability of oxygen, named Warburg effect. Cytoplasmic pyruvate is, in major part, converted into lactate. The Wnt/beta-catenin pathway induces also the transcription of genes involved in cell proliferation, cell invasiveness, nucleotide synthesis, tumor growth and angiogenesis, such as cMyc, cyclin D1, PDK. In addition, in gliomas cells, PPAR gamma is downregulated, leading to a decreased in insulin sensitivity and an increased in neuroinflammation. Moreover, PPAR gamma contributes to regulate some key circadian genes. Abnormalities in the regulation of circadian rhythms and dysregulation in circadian clock genes are observed in gliomas. Circadian rhythms are dissipative structures, which play a key role in far-from-equilibrium thermodynamics through their interactions with Wnt/beta-catenin pathway and PPAR gamma. In gliomas, metabolism, thermodynamics and circadian rhythms are tightly interrelated.